An evaluation on the application of the flipped classroom model in teaching English at a university in Hanoi = Đánh giá hiệu quả ứng dụng mô hình lớp học đảo ngược trong giảng dạy tiếng Anh tại một trường đại học ở Hà Nội - Trần, Thị Hậu (2020)
This study attempts to evaluate the effect of a flipped classroom model in TOEIC teaching for third-year students at Hanoi Industrial Textile Garment University (HTU). The study employed the approach of experimental research to examine the effectiveness of using flipped classroom in teaching TOEIC at HTU. The TOEIC course was trial taught for two co-horts: one employed flipped classroom model (teaching methodology) and the other used the traditional lecture-based classroom model. As well, a comparison of the quantitative results of students’ test scores was utilized to compare the academic achievement between the two teaching methodologies. In addition, questionnaire-based survey was conducted to explore students’ perception and satisfaction in the flipped classroom learning environment. Last but not least, case study interviews for both teachers and students involved in flipped classroom was carried out to understand their views on the implementation of flipped classroom in real teaching condition. The findings from the study serve as an important fundament for HTU teachers to evaluate the efficacy of flipped classroom in teaching TOEIC and how it needs to be implemented properly in reality.